OCP Java SE 8 programmer II exam guide (Exams 1Z0-809) - Sierra, Kathy; Bates, Bert; Robson, Elisabeth (McGraw-Hill Education, 2018)
Written by a team of experts, including two developers of the original exam, OCP Java SE 8 Programmer II Exam Guide (Exam 1Z0-809) offers comprehensive coverage of every subject on the test and lays out essential Java programming skills. Throughout, step-by-step exercises; self-tests; and "Exam Watch," "Inside the Exam," and "On the Job" sections highlight salient points and aid in learning. In all, the book and accompanying digital content feature more than 350 practice questions that mirror those on the live test in tone, format, and content--